Analysis of relevant normative documents on oil sludge treatment and disposal - CHEN Zhong*; XU Fenglin; YANG Demin; WANG Chaoqiang; XIE Jiacai; MEI Xudong; TAN Xun; TONG Kun* (能源环境保护)
Oily sludge, a mixture of oil, water and solid, is an important waste generated from the oil and gas industry. It is usually classified as hazardous waste because it contains inflammable and toxic substances, such as petroleum hydrocarbons, heavy metals, and polycyclic aromatic hydrocarbons. It is expected that the amount of produced oily sludge will continue to increase due to the increasing exploitation of unconventional oil and gas resources. In the past few years, normative documents related to oily sludge have been increasingly updated and published, including the laws and regulations, policy guidelines, and standards. These documents are important for all aspects of oily sludge treatment and disposal technology, such as research and development, screening, and commercialization. Therefore, a total of 58 normative documents have been searched and collected. Based on these, the classification and definition of oily sludge types in the past editions of the National Hazardous Waste List are compared. Furthermore, the latest classification and characteristics identification process are summarized, and the national and local management regulations on environmental protection of oil and gas exploration and development are listed. The pollution prevention technology policy and the environmental management guide for hazardous waste are analyzed, with all national, industrial, and local standards discussed. Finally, a schematic diagram of the technical process for oily sludge treatment and disposal is drawn, and suggestions are given for further improvement of the normative documents. The results can provide reference and inspiration for environmental management, process selection, and research and development of treatment and disposal technology.